Acid-catalyzed synthesis of pyrazolo[4, 3-c]quinolines from (1H-pyrazol-5-yl)anilines and ethers via the cleavage of C–O bond. (22nd October 2022) - Mu, Yangxiu; Jiang, Rui; Hong, Yu; Hou, Jing; Yang, Zhixiang; Tang, Dong
Abstract: Acid-promoted the cyclization reaction for the synthesis of pyrazolo[4, 3-c]quinolines from (1H-pyrazol-5-yl)anilines and ethers via the cleavage of C–O bond has been developed. This method exhibits the advantages of good functional group tolerance, simple reaction conditions and without addition of metal catalyst, providing novel products in moderate to good yields, which has potential applications in the organic, pharmaceutical chemistry. Graphical abstract: This strategy provide a method for the synthesis of pyrazolo[4, 3-c]quinoline from (1H-pyrazol-5-yl)anilines and ethers via the cleavage of C–O bond and achive good functional group tolerance without the addtion of metal catalyst under simple reaction conditions.